Corporate social responsibility in a competitive business environment - Carol Newman; John Rand; Finn Tarp; Neda Trifkovic (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
Using a specially designed survey instrument in combination with a representative sample of Vietnamese enterprises, we explore firm-level efficiency effects of corporate social responsibility. We find a positive relationship between adoption of corporate social responsibility initiatives and firm efficiency, and reveal that the impact is stronger for firms in non-competitive industries. Moreover, we show that local community focused corporate social responsibility initiatives drive the aggregate effect. This suggests that socially responsible actions by firms are likely to pay-off when stakeholder engagement has a localized focus. We provide evidence of reciprocity by showing that employees accept a lower share of additionally generated value added in exchange for working in a company that signals 'good' corporate values.
Keywords: O12; O14; O35; O53; 330; firm efficiency; manufacturing; corporate social responsibility; Viet Nam